2022
DOI: 10.3390/vaccines10111899
|View full text |Cite
|
Sign up to set email alerts
|

Hesitancy toward the Full COVID-19 Vaccination among Kidney, Liver and Lung Transplant Recipients in Italy

Abstract: Background: Coronavirus disease 2019 (COVID-19) vaccination hesitancy is a threat as COVID-19 vaccines have reduced both viral transmission and virus-associated mortality rates, particularly in high-risk subgroups. Solid organ transplant recipients (SOTRs) are particularly vulnerable, as the underlying causes of their organ failure and the chronic immunosuppression are associated with a lower immune response to COVID-19 vaccines, and with an excessive risk of death due to SARS-CoV-2 infection. We aimed to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…Reasons for this hesitancy have yet to be investigated. An Italian working group conducted a questionnaire study in which fear of adverse events and perceived lack of efficacy were found to be the main reasons for hesitancy [ 24 ]. Although less than half of the patients received a fourth vaccination, half of them had a COVID-19 infection during the observation period.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for this hesitancy have yet to be investigated. An Italian working group conducted a questionnaire study in which fear of adverse events and perceived lack of efficacy were found to be the main reasons for hesitancy [ 24 ]. Although less than half of the patients received a fourth vaccination, half of them had a COVID-19 infection during the observation period.…”
Section: Discussionmentioning
confidence: 99%
“…In May 2021 in China, 77.2% of 813 OTR surveyed were classified as vaccine-hesitant, and only 5.7% were vaccinated at the time [22]. On the contrary, in early 2022, of 1019 OTR surveyed at a single center in Italy who had already received 2 immunizations and were eligible for a third, only 5% were considered hesitant [9].…”
Section: Discussionmentioning
confidence: 99%
“…Vaccine hesitancy encompasses a spectrum of beliefs that result in indecision, ambivalence, or resistance to a given vaccine. Its wide range of causes includes barriers to access, medical misinformation or lack of information, concerns regarding adverse effects, administration mechanisms, efficacy against infection, and mistrust in the medical system, drug testing process, or the state [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Although patients with CKD were prioritized during vaccination rollout, vaccine hesitancy, shortages and mass vaccine distribution challenges were reported to be barriers to successful achievement of global vaccination rates [75]. Similar to data from the general population, surveys conducted among dialysis patients as well as kidney transplant recipients include a lack of confidence in vaccine efficacy, concerns about safety, scepticism about healthcare systems [76,77].…”
Section: Covid-19 Vaccination Hesitancymentioning
confidence: 99%